(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
This study focuses on a problem of hospital transaction such as registering and viewing a record manually that caused of missing out the record of Patient information and can’t connect in other modules by integration in every department operation. The proponent’s solution is focuses on creating computerized, integrated, real time -user friendly and cost-effective system that can help the employees managing and maintaining all the hospital’s transaction easily. Agile Scrum is a process commonly used for product development, especially for software development. Product Owner is the project’s key that represents users, customers. Scrum Master is responsible for the team productive and helping the team uses the scrum process. The product backlog is a features list that shows of desired features product. Sprint Planning Meeting is held during the product owner represents the most items on the product backlog. The proponent’s findings are pivotal in terms of solving a different problem in this study. Hospitals currently use a manual system for maintenance of critical information. Multiple copies of the same patient information exist in the hospital they may lead to inconsistency in various data stores. The proponents came up with a very effective solution to solve the needs of a hospital transaction as well as the employees manage it. The top problem encountered of patient registration and doctor’s appointment is lack of doctor’s appointment scheduling and storing patient info manually where the employees struggle standardize data. The proponents conclude a comprehensive Integrated Information system that helps the process, managing and facilitate all the aspects of the hospital. All of this information must be managed in an efficient may be effectively utilized Core transaction 1 will automate management of the hospital making it more efficient and it aims data integrity and consolidating data. The proponents recommend that the problem in a system could be solved to study an existing system and find a basis to create and assign the person who maintains in a system better and secure to help user good services. The proponents recommend this system is user-friendliness, reliable, accurate and real-time process.